COMPARAÇÃO DO AUMENTO DE FORÇA MUSCULAR POR ISOMETRIA, ASSOCIADA OU NÃO À ESTIMULAÇÃO RUSSA (Fiep Bulletin - online, 2011)
The neuromuscular electrical stimulation (NMES) is a non-invasive therapeutic procedure, with the purpose of producing muscular contraction. It is very used in the clinical practice favoring the strengthening and muscular hypertrophy in the healing process of diseases, it also improves physical conditions and esthetic aspects. The applying technique is critical to the effectiveness of the results. This research's goal is to verify if an active exercise is more efficient when associated to a neuromuscular electrical stimulation. In the process, 14 volunteering subjects participated, those were adequate to the criteria of inclusion/exclusion, divided into two groups: G1 – verify the effectiveness of the treatment with isometrics isolated; G2 – verify the effectiveness of the treatment with isometrics associated to NMES on Russian current. The treatment lasted 20 minutes for both groups, with 9 seconds of isometrics contraction and 9 seconds of relaxation, however, in the second group it was associated to the device in a frequency of 2500Hz modulated to 30Hz to activate fibers type I and 50Hz to activate fibers type II, with the maximum supported dose. All subjects were evaluated and revaluated with a dynamometer, in the beginning, the middle and the end of the treatment, in a total of 12 sessions. The average of the increasing for the G1 was of 3,12 Kg / s, for G2, 7,82 Kg / s. Through the obtained results, we may conclude that both groups obtained an increase in progressive muscular strength, but only the second group it was significant to this research, with a difference between them of 24,84%, making the application of Russian stimulation important for the muscular strengthening.
Keywords: estimulação elétrica; corrente russa; força muscular